2021
DOI: 10.26717/bjstr.2021.34.005531
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi, Qigong and the Treatment of Disease

Abstract: Qigong has been around for more than 4,000 years. It contains aspects of martial arts, philosophy, theology, mindfulness, meditation, exercise, and Traditional Chinese Medicine (TCM). It is a subfield of both tai chi and health economics. Practicing qigong exercises on a regular basis can improve health and cause the body to function more efficiently. Thus, it is also a subfield of applied microeconomics in the sense that it increases efficiency. Numerous medical studies have been done on the effect of qigong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Currently, the clinical application of Qigong exercise is primarily con ned to outpatient settings for individuals with depression or anxiety. [19][20][21][22][23] Advocates of this exercise assert that it aids in blood pressure and sleep regulation, augments muscle strength, and alleviates anxiety and depression levels in patients with anxiety disorders, major depression, post-traumatic stress disorders, and burn-out syndrome (Abbott&Lavretsky, 2013; Guo et.al.,2018;Oh et. al.,2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, the clinical application of Qigong exercise is primarily con ned to outpatient settings for individuals with depression or anxiety. [19][20][21][22][23] Advocates of this exercise assert that it aids in blood pressure and sleep regulation, augments muscle strength, and alleviates anxiety and depression levels in patients with anxiety disorders, major depression, post-traumatic stress disorders, and burn-out syndrome (Abbott&Lavretsky, 2013; Guo et.al.,2018;Oh et. al.,2013).…”
Section: Introductionmentioning
confidence: 99%
“…Qigong exercise, integrating mindfulness and meditative movement, is an ancient Chinese medical practice for relaxation, stress reduction, diversion from negative thoughts, enhanced blood ow, and improved emotional wellbeing (Motivala et al,2006;Niles et.al.,2022) Qigong exercise encompasses ve key elements: Visualization, meditation, relaxation, deep breathing, and energy (Qi) circulation. Approximately 60 million individuals in China presently engage in daily Qigong exercise (Chang et.al.,2018;McGee, 2021). Studies comparing Qigong exercise with PMR indicated that while the former was more effective in somatic effects, the latter demonstrated greater prominence in psychological effects (Alizadeh et al,2013;Georgiev et al,2012;Petruzzello et al,1991).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, there are some literature works that touch upon Chinese culture utilizing ChatGPT. [3] However, these existing publications only scratch the surface of the topic. For example, one publication engages in dialogue with ChatGPT, focusing on the strengths and limitations of qualitative exchanges.…”
Section: Introductionmentioning
confidence: 99%